Lingering Sound: Event-Related Phase-Amplitude Coupling and Phase-Locking in Fronto-Temporo-Parietal Functional Networks During Memory Retrieval of Music Melodies - Tseng, Yi-Li; Liu, Hong-Hsiang; Liou, Michelle; Tsai, Arthur C.; Chien, Vincent S. C.; Shyu, Shuoh-Tyng; Yang, Zhi-Shun (Frontiers in Human Neuroscience, 2019)
Brain oscillations and connectivity have emerged as promising measures of evaluating memory processes, including encoding, maintenance, and retrieval, as well as the related executive function. Although many studies have addressed the neural mechanisms underlying working memory, most of these studies have focused on the visual modality. Neurodynamics and functional connectivities related to auditory working memory have yet been well established. In this study, we explored the dynamic of high density (128-channel) electroencephalography (EEG) in a musical delayed match-to-sample task (DMST), in which thirty-six participants were recruited and were instructed to recognize and distinguish the target melodies from similar distractors. Event-related spectral perturbations (ERSPs), event-related phase-amplitude coupling (ERPAC), and phase-locking value (PLV) were used to determine the corresponding brain oscillations and connectivities. First, we observed that low-frequency oscillations in the frontal, temporal, and parietal regions were increased during the processing of both target and distracting melodies. Second, cross-frequency coupling between low-frequency phase and high-frequency amplitude was elevated in the frontal and parietal regions when the participants were distinguishing between the target and distractor, suggesting that phase-amplitude coupling could be an indicator of the neural mechanisms underlying memory retrieval. Finally, phase-locking, an index evaluating brain functional connectivity, revealed that there was fronto-temporal phase-locking in theta band and fronto-parietal phase-locking in alpha band during the recognition of both the two stimuli. These findings suggest the existence of functional connectivity and phase-amplitude coupling in the neocortex during musical memory retrieval, and provide a highly resolved timeline to evaluate brain dynamics. Furthermore, inter-regional phase-locking and phase-amplitude coupling among the frontal, temporal and parietal regions occurred at the very beginning of musical memory retrieval, which might reflect the precise timing when cognitive resources are involved in the retrieval of targets and the rejection of similar distractions. To the best of our knowledge, this is the first EEG study employing a naturalistic task to study auditory memory processes and functional connectivity during memory retrieval, by which can shed light on the use of natural stimuli in studies that are closer to the real-life applications of cognitive evaluations, mental treatments, and brain-computer interface.